PEMBACAAN FALSAFAH WUJUDIYAH DALAM RELASI PEMIKIRAN HAMZAH FANSURI DAN MULLA SADRA - Teuku Raja Idin (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2022)
This paper is a literature review of the thoughts of Mullā Ṣadrā and Hamzah Fansuri regarding the philosophical discourse of embodiment which is considered to have a relationship in the discourse of Islamic philosophy and the archipelago. This paper aims to read and explain the philosophical relation of the embodiment of Hamzah Fansuri and Mullā Ṣadrā as models of Nusantara and Islamic thought which are seen as having a relationship or similarity. By using a descriptive analysis approach, it is concluded that being in the view of Hamzah Fansuri and Mullā Ṣadrā is seen as a source of existence that is one in diversity. One source of existence is understood as existence that presents various entities outside of itself. Mullā Ṣadrā and Hamzah Fansuri understand that the universe consists of a series of causes and effects that imply the diversity of existence in reality. The diversity of existence comes from the main cause called Wājib al-Wūjūd which describes existence as the source of one being in diversity. The result of this paper is to read the urgency of Hamzah Fansuri's and Mullā Ṣadrā's philosophy of being who is seen as having a relationship or similarity in philosophical civilization, as well as tracing the interaction of the discourses of Nusantara and Islamic thought.